A comparison of East and West German media coverage of the 1976 Olympic Games in Montreal - Manfred Massing; Dieter Voigt (Communicare)
During recent years there was a perceptible tendency towards the political and ideological use of sports journalism. The present study deals with this problem, and comprises a comparative analysis of the media coverage of the 1976 Olympic Games in Montreal by East and West German media. There is a close interaction between sports and the media, with benefits for both. Top performance sports as such is not only very interesting, but the contest for medals, cups, and new records draws the attention of millions of people. These are also the people who are interested in the products of any medium. Whereas local sports draws local audiences, top performance sports not only draws national, but also international audiences.